2013
DOI: 10.1182/blood-2012-08-449181
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α is a protective factor in conditional PHD2-deficient mice suffering from severe HIF-2α–induced excessive erythropoiesis

Abstract: Erythropoiesis must be tightly balanced to guarantee adequate oxygen delivery to all tissues in the body. This process relies predominantly on the hormone erythropoietin (EPO) and its transcription factor hypoxia inducible factor (HIF). Accumulating evidence suggests that oxygen-sensitive prolyl hydroxylases (PHDs) are important regulators of this entire system. Here, we describe a novel mouse line with conditional PHD2 inactivation (cKO P2) in renal EPO producing cells, neurons, and astrocytes that displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 71 publications
(114 citation statements)
references
References 50 publications
10
102
1
1
Order By: Relevance
“…The CD68:cre mouse line and detailed characterization of the CD68:cre-PHD2 f/f (cKO) line were shown in a recent report from our research group. 16 All mice used in this report were born in a normal Mendelian manner. Mouse strains were backcrossed to C57BL/6 at least 9 times.…”
Section: Methods Micementioning
confidence: 99%
See 2 more Smart Citations
“…The CD68:cre mouse line and detailed characterization of the CD68:cre-PHD2 f/f (cKO) line were shown in a recent report from our research group. 16 All mice used in this report were born in a normal Mendelian manner. Mouse strains were backcrossed to C57BL/6 at least 9 times.…”
Section: Methods Micementioning
confidence: 99%
“…To conditionally ablate PHD2 in the hematopoietic system, we combined the PHD2 floxed line with the recently described CD68: cre line to obtain cKO mice. 16 Next to a subset of epithelial cells and erythropoietin-producing cells in kidney and brain, PHD2 is also significantly reduced in the entire BM in this cKO strain. However, no significant decrease of PHD2 was seen in endothelial cells, fibroblasts, or lysates of several nonhematopoietic organs.…”
Section: Generation Of Hematopoietic Conditional Phd2 Deficient Micementioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this discrepancy has not been extensively tested, but invertebrate data suggest engagement of HIFs in the modulation of ageing rates. Moreover, HIFs' transactivation targets include genes with known neuroprotective products, although it has been suggested that these TFs might play either protective or detrimental roles [54,86,140,223].…”
Section: Transcriptional and Post-transcriptional Regulators As Sirtumentioning
confidence: 99%
“…Mechanistically, IGF2 upregulates VEGF by increasing the expression of hypoxia-inducible factor-1a (HIF1a), a master regulator of cellular and systemic homeostatic response to hypoxia. Interestingly, HIF1a itself has been shown to play a protective role in various experimental settings of apoptosis, including islet transplantation (Kim & Kim 2005, Czibik et al 2009, Franke et al 2013, Stokes et al 2013. To our knowledge, there have been no studies aiming to identify whether a synergistic role of IGF2 with HIF1a exists in the context of islet transplant survival; Cell signalling pathways activated in the pancreatic islets following pro-inflammatory cytokine exposure.…”
Section: Apoptosis In Islet Transplantation: the Role For Pro-inflammmentioning
confidence: 99%